Movement form of the overarm throw for children at 6, 10 and 14 years of age. Issue 9 (2nd September 2021) - Palmer, Hannah A.; Newell, Karl M.; Mulloy, Franky; Gordon, Dan; Smith, Lee; Williams, Genevieve K. R.
Abstract: This study investigated overarm throwing technique at different developmental ages in children from the perspective of three distinct, though potentially complementary, approaches to motor skill acquisition. Children at 6, 10, and 14 years of age ( N  = 18), completed dominant overarm throws during which whole-body kinematic data were collected. Firstly, application of Newell's ([1985]. Coordination, control and skill. In Advances in Psychology (Vol. 27, pp. 295–317). North-Holland.) stages of learning identified three distinct age-related coupling modes between forward motion of the centre-of-mass (CoM) and the wrist, which demonstrated a greater range of couplings for older children. Secondly, in line with Bernstein's ([1967]. The coordination and regulation of movement . London: Pergamon Press.) hypothesis of freezing before freeing degrees of freedom, a significantly smaller range of motion (ROM) at the ankle and knee joints, but greater ROM at the hip and upper limb joints was found for the 6 year old group compared to the 10 and 14 year old groups. Thirdly, based on the components model (Roberton & Halverson [1984]. Developing children-their changing movement: A guide for teachers . Lea & Febiger.), the overarm throws demonstrated by 6 year olds were characterised as primitive to intermediate, where 10 and 14 year old's throws were characterised by the penultimate action level for each component. Characteristics of CoM-wrist coupling more clearly identify children's age-related technique and highlight the importance of posture-ball release dynamics. The posture-ball dynamics were supported by changes in ROM and the components model, revealing the complementary nature of the three approaches to the analysis of age-related differences in overarm throwing action.